2022
DOI: 10.1063/5.0123623
|View full text |Cite
|
Sign up to set email alerts
|

Electrically tuning near-field heat flux using metal–oxide–semiconductor structure considering gradient dielectric function distribution

Abstract: We build a model to determine the dependency of near-field heat flux on bias voltage using the metal–oxide–semiconductor structures considering gradient distribution of dielectric function. Quantitative dependency of near-field heat flux exchanged by two biased metal–oxide–semiconductor structures on bias voltage is established. The distribution of carrier density and the resultant dielectric function in the semiconductor layer caused by the bias are determined. The corresponding near-field heat flux is calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…[1][2][3] However, the radiative heat transfer can break the black-body limit and exceed the limit by several orders of magnitude when two objects are separated at a distance less than the characteristic thermal wavelength. [4][5][6][7][8][9][10][11] This is mainly due to the contribution of evanescent waves, which significantly influence the near-field radiative heat transfer (NFRHT). [12][13][14][15][16][17] Previous studies have demonstrated NFRHT can be enhanced between materials supporting surface wave resonances and hyperbolic phonon polaritons (HPPs).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] However, the radiative heat transfer can break the black-body limit and exceed the limit by several orders of magnitude when two objects are separated at a distance less than the characteristic thermal wavelength. [4][5][6][7][8][9][10][11] This is mainly due to the contribution of evanescent waves, which significantly influence the near-field radiative heat transfer (NFRHT). [12][13][14][15][16][17] Previous studies have demonstrated NFRHT can be enhanced between materials supporting surface wave resonances and hyperbolic phonon polaritons (HPPs).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is increasing interest in materials with gradient permittivity, particularly in one-dimensional systems, due to their capacity to enhance heat flux in both near-and far-field thermal applications through unique physical characteristics. [21][22][23] For instance, Zhao et al's study on NFRHT between two gradient permittivity slabs highlights enhanced energy transmission in the lower frequency range, attributed to the red-shift effect of internal polaritons. 21 However, the adjustable parameters of these bulk materials are relatively limited, posing constraints on their flexibility and control.…”
Section: Introductionmentioning
confidence: 99%